Implementation Of Facilities And Infrastructure Management At Sdn 100720 Sihopuk Baru Village - Hasriyati Harahap; Muhammad Fadhli (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2022)
This study aims to describe the implementation of facilities and infrastructure management at SDN 100720 Sihopuk Baru Village. With a qualitative approach and field study method, data were collected through interviews, observations, and document studies. The results of the study indicate that the management of facilities and infrastructure in schools still faces various obstacles, such as limited classrooms, library facilities, UKS, and learning media. The management process from planning to deletion is not optimal. This study recommends improving overall facility management and support from schools and policy makers to create a more conducive learning environment.